Avaliação da cinética de degradação abiótica do polietileno de alta densidade, na presença e ausência de aditivo pró-degradante e estabilizantes - Lellis, Marcela Caroline Antunes (2016)
The convenience of single-use packaging of high density polyethylene (HDPE) led to the need to convert them into biodegradable materials in less time to minimize the environmental problems caused by disposal. An alternative is the use of prodegradants. However, mechanical properties of packaging materials must be preserved during use and pro-degrading action should increase only after disposal. To achieve this balance between performance and degradability, stabilizers can be added to HDPE/prodegradant. HDPE is a chemically stable polyolefin, hence abiotic degradation times, even in the presence of prodegradant, are long. Therefore, the need for kinetic studies has become critical. To this end, formulations with different manganese stearate levels (50, 200 and 400 ppm) in the presence or absence of stabilizers (primary and secondary) were subjected to thermo-oxidative degradation at three temperatures (60, 70 and 80 °C). For the development of the kinetic studies, tensile tests, infrared spectroscopy and size exclusion chromatography were performed at different thermo-oxidation times. The results showed that manganese stearate, regardless of concentration, in addition to accelerating thermal oxidation of HDPE caused a higher level of degradation, characterized by lower molar masses and higher levels of carbonyl index at the end of the degradation time. Addition of the primary stabilizer increased induction time without altering degradation rates, which enables it to be used in conjunction with the prodegradant to delay the onset of the degradative process. However, the secondary stabilizer caused no significant difference for the levels studied. The kinetic assessment (Arrhenius extrapolations) allowed us to conduct studies predicting degradation times relevant to the analysis of degradation.